Stress Granule Assembly Is Mediated by Prion-like Aggregation of TIA-1 - Gilks, Natalie (The American Society for Cell Biology, 2004)
TIA-1 is an RNA binding protein that promotes the assembly of stress granules (SGs), discrete cytoplasmic inclusions into which stalled translation initiation complexes are dynamically recruited in cells subjected to environmental stress. The RNA recognition motifs of TIA-1 are linked to a glutamine-rich prion-related domain (PRD). Truncation mutants lacking the PRD domain do not induce spontaneous SGs and are not recruited to arsenite-induced SGs, whereas the PRD forms aggregates that are recruited to SGs in low-level–expressing cells but prevent SG assembly in high-level–expressing cells. The PRD of TIA-1 exhibits many characteristics of prions: concentration-dependent aggregation that is inhibited by the molecular chaperone heat shock protein (HSP)70; resistance to protease digestion; sequestration of HSP27, HSP40, and HSP70; and induction of HSP70, a feedback regulator of PRD disaggregation. Substitution of the PRD with the aggregation domain of a yeast prion, SUP35-NM, reconstitutes SG assembly, confirming that a prion domain can mediate the assembly of SGs. Mouse embryomic fibroblasts (MEFs) lacking TIA-1 exhibit impaired ability to form SGs, although they exhibit normal phosphorylation of eukaryotic initiation factor (eIF)2α in response to arsenite. Our results reveal that prion-like aggregation of TIA-1 regulates SG formation downstream of eIF2α phosphorylation in response to stress.